Relationship between the water-exchangeable fraction of PAH and the organic matter composition of sediments. (December 2016) - Belles, Angel; Alary, Claire; Mamindy-Pajany, Yannick; Abriak, Nor-Edine
Abstract: The sorption of PAH on 12 different sediments was investigated and was correlated to their corresponding organic matter (OM) content and quality. For this purpose, the OM was precisely characterized using thermal analysis consisting in the successive combustion and quantification of the increasingly thermostable fractions of the OM. Simultaneously, the water-exchangeable fraction of the sorbed PAH defined as the amount of PAH freely exchanged between the water and the sediment (by opposition to the PAH harshly sorbed to the sediments particles) was determined using a passive sampler methodology recently developed. The water concentrations, when the sediment-water system is equilibrated, were also assessed which allows the determination of the sediment-water distribution coefficients without artifacts introduced by the non water-exchangeable fraction of PAH. Hence, the present study provides the distribution coefficients of PAH between the water and 4 different OM fractions combusted at a specific temperature range. The calculated distribution coefficients demonstrate that the sedimentary OM combusted at the intermediate temperature range (between 300 °C and 450 °C) drives the reversible sorption of PAH while the inferred sorption to the OM combusted at a lower and higher temperature range does not dominate the partitioning process. Graphical abstract: Highlights: The exchangeable fraction of PAH ranges from 3 to 100% depending of PAH and sediment. The OM combusted above 450 °C drives the desorption-resistant fraction of PAH. The OM combusted between 300 °C and 450 °C drives the reversible sorption of PAH. Abstract : The sedimentary OM combusted between 300 °C and 450 °C drives the reversible sorption of PAH.